Minimal State and the Water Issue in the Qajar Era, Pre- Constitutional Age - Mehdi Mirkiaee (دولت‌پژوهی, 2023)
Water issue" has been one of the main issues of Iranian human life throughout history, and the research about it can shed light on various aspects of the political, economic and social life of Iranians. Artificial irrigation has long been one of the necessities of people's lives in this semi-arid climate. The dispersion of water resources, which was subject to dispersion of the population, required the country to have an innumerable number of dams, aqueducts, reservoirs, wells and streams. Building a dam to store water and control floods and building aqueducts, which sometimes reached tens of kilometers in length, required spending a lot of money and a lot of labor. At first glance, the government was expected to be responsible for the creation and repair of water facilities as institution that has the most resources of the country. The question is, considering that pre-modern governments played a minimal role in solving people's problems and providing their necessities of life, to what extent did the Qajar government accept responsibility for the creation and repair of these facilities in the territory of Iran? What evidence confirms the minimal involvement of Qajar government in the water issue? What were the reasons for the non-interference of the government in water supply and how could the people be responsible for solving this problem? Our assumption is that the Qajar government did not consider itself obligated to provide water to villages, farms and even cities with minimal interference in civil affairs, and the countless number of dilapidated dams and aqueducts is a sign that the government has a duty in this field for He did not imagine and only in a few cases where he was sure that the profit would quickly reach the treasury, he accepted a small investment. In the meantime, the further some areas were from the center, the less government intervention in their irrigation systems. Also, the Qajar government looked at the water issue as an opportunity for earning money by selling running water and collecting taxes from other water sources. Governors of the provinces were also interested in creating irrigation system for their fields only if they were the owners of land in that province. In the meantime, the main burden of creating and maintaining water facilities was the responsibility of the people, who mainly provided the expenses to the landlords and the labor to the subjects. The tradition of endowment was another factor that weakened the role of the government in this field. People's participation in the construction and repair of dams, aqueducts, reservoirs and streams, as well as group oppressions and settlements, as well as collective conflicts, along with the management of water distribution and the selection of Mirabs, led to the emergence of self-organized groups and circles and their greater cohesion in society. Previously, the views of people like Karl Marx and Karl August Wittfogel about the active involvement of Asian governments in solving the water problem in semi-arid climates had gained supporters. Marx believed that in these areas, governments took control of limited water resources and established water supply security, and by managing water resources, they made the producers highly dependent on themselves, and made the government subjects critical. Influenced by him, Wittfogel also realized the need of these communities for huge water supply facilities that only the government could cover. He knew the first and fundamental factor of the formation of the absolute power of the government in these regions. In our research, we have tried to show by relying on a lot of data from the history of Qajar era Iran that not only the government was not involved in many waters supply matters, but also the realities and limitations of the pre-modern world, the Qajar government in planning to intervene in the water issue, especially in remote areas. From the center, he was disabled. This research was done with descriptive-explanatory method and using the documents, especially the petitions of the Majlese Tahqiqe Mazalem. The theoretical framework of the research is derived from Patricia Crone's point of view about the minimal government in the pre-modern world. Previously, no independent research has been conducted on the minimal role of the Qajar government in the water issue.